Pengaruh Manajemen Laba Terhadap Nilai Perusahaan Dengan Komite Audit Sebagai Variabel Moderasi - Rohmawan, Mohamad Fadilah; Herawati, Tuti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The objective of this study is to analyze the effect of earnings management on firm value with the audit committee as a moderating variable. The population in this study consists of companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample consists of 124 data points from 31 companies selected using purposive sampling and based on secondary data. The analytical methods employed are panel data analysis using the fixed effect model and moderated regression analysis. The results show that earnings management has a significant positive effect on firm value and the audit committee is able to act as a moderating variable in the relationship between earnings management and firm value.